Elsa & Fred [videorecording (DVD)] - Radford, Michael, 1946-; MacLaine, Shirley, 1934-; Plummer, Christopher; Bakula, Scott ([Publisher not identified], 2014)
The story of two people who, at the end of the road, discover that it's never too late to love. After losing his wife, Fred feels disturbed, confused and alone, so his daughter helps move him into a small apartment where he meets Elsa. From that moment on, everything changes. Elsa bursts into Fred's life like a whirlwind, determined to teach him that the time he has left to live, be it more or less, is precious and that he should enjoy it as he pleases.